Bacterium‐Templated Polymer for Self‐Selective Ablation of Multidrug‐Resistant Bacteria. (11th June 2020) - Qi, Guobin; Hu, Fang; Kenry,; Chong, Kok Chan; Wu, Min; Gan, Yunn Hwen; Liu, Bin
Abstract: The recognition and inactivation of specific pathogenic bacteria remain an enormous scientific challenge and an important therapeutic goal. Therefore, materials that can selectively target and kill specific pathogenic bacteria, without harming beneficial strains are highly desirable. Here, a material platform is reported that exploits bacteria as a template to synthesize polymers with aggregation‐induced emission (AIE) characteristic by copper‐catalyzed atom transfer radical polymerization for self‐selective killing of the bacteria that templates them with no antimicrobial resistance. The bacteria‐templated polymers show very weak fluorescence in aqueous media, however, the fluorescence is turned on upon recognition of the bacteria used as the template to synthesize the polymer even at a low concentration of 600 ng mL −1 . Moreover, the incorporated AIE fluorogens (AIEgens) can act as an efficient photosensitizer for reactive oxygen species (ROS) generation after bacteria surface binding, which endows the templated polymers with the capability for selective bacterial killing. The bacterium‐templated synthesis is generally applicable to a wide range of bacteria, including clinically isolated multidrug‐resistant bacterial strains. It is envisioned that the bacterium‐templated method provides a new strategy for bacteria‐specific diagnostic and therapeutic applications. Abstract : A material platform that exploits bacteria as a template to synthesize polymers with aggregation‐induced emission characteristic is reported. The bacterium‐templated polymer shows very weak fluorescence in aqueous media and the fluorescence is turned on upon recognition of the templated bacteria. The incorporated AIEgen can act as an efficient photosensitizer which endows the templated polymers with capability for selective bacterial killing.